Neuromuscular function of the shoulder girdle and upper extremity musculature in individuals with a history of glenohumeral labral repair. (2nd June 2022) - Takeno, Katsumi; Ingersoll, Christopher D.; Glaviano, Neal R.; Khuder, Sadik; Norte, Grant E.
Abstract : The purpose of this study was to compare neuromuscular function in the upper extremity musculature between individuals with glenohumeral labrum repair and uninjured controls. This cross‐sectional study examined 16 individuals with a primary, unilateral glenohumeral labral repair (male/female: 13/3, age: 24.1 ± 5.0 years, time from surgery: 36.7 ± 33.3 months) and 14 uninjured individuals (male/female: 11/3, age: 23.8 ± 2.7 years) matched by age, sex, activity level, and limb dominance participated. Mass‐normalized shoulder abduction and wrist flexion maximal voluntary isometric contraction (MVIC) torque, motoneuron pool excitability of the flexor carpi radialis (Hoffmann reflex), and corticospinal excitability of the upper trapezius, middle deltoid, and flexor carpi radialis (active motor threshold [AMT]) were evaluated. Dependent and independent t ‐tests were used to assess between‐limb and between‐group comparisons. Cohen's d effect sizes with 95% confidence intervals were used to quantify the magnitude of differences observed. Within the injured group, the involved limb had lesser shoulder abduction MVIC torque ( p < 0.001, d = 1.16) and higher AMT for the upper trapezius ( p = 0.01, d = 0.81) compared with the contralateral limb. The labral repair group had lesser shoulder abduction MVIC torque ( p < 0.001, d = 1.17) and Hoffmann reflex ( p = 0.01, d = 0.99), as well as higher AMT for the upper trapezius ( p < 0.001, d = 1.23) in their involved limb compared with the control group. Large magnitude neuromuscular impairments are present beyond 6 months from glenohumeral labral repair, suggesting potential origins of impairments to be addressed during post‐operative rehabilitation.